FIELD TEST, RESEARCH AND RESULTS OF A FLEXIBLE MACHINE WITH A ROTOR: “Agromechanika” Scientific Research Institute - Qurbanov, Huseyn (Journal of Agricultural Sciences (Belgrade), 2024)
Science-based farming systems have proven that after plowing, the soil layer contains from 100-200 million to 2-3 billion weed seeds per hectare, 70-90% of which can be destroyed by  harrows before and after emergence.Pre-sowing cultivation with rotor trowels leads to the development of seeds in the soil and the creation of aeration process for the root system during the growing season, which improves plant development and productivity.    A flexible trowel with a rotor was developed in our laboratory.Constructive and technological parameters were analyzed using the experimental planning method and optimal results were obtained.The diameter of the rotor and the speed of the unit are taken as the main influencing factors.The "percentage of lumps crushing" is the output parameter, and the "soil moisture" is the input parameter.The regression equation and diagrams were obtained from the mathematical analysis.Optimally, based on 4 experiments, the unit speed V=15 km/h, cultivation depth 5...10 cm, rotor diameter D=380 mm were selected. The technological operations carried out with a flexible trowel with a rotor make 81.28 % of the lumps crushing in the soil, which has a significant effect of 95% on the development of the sown seeds.In the field test, the degree of "lumps crushing " was studied in the soil with a moisture content of 18...24%.It was found that the fraction of soil less than 10 mm is 51% of it.The size of the lumps is 10...25; Those of 25...50 and 50...100 mm make up 18, 13 and 14% of the soil, respectively.The size of lumps above 100 mm make up 4% of the soil.
Keywords: machine; lumps crusing; soil; rotor; flexible trowel